1998
DOI: 10.1016/s0002-9440(10)65604-0
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Microvascular Injury in the Human Peripheral Blood Lymphocyte Reconstituted-Severe Combined Immunodeficient (HuPBL-SCID) Mouse/Skin Allograft Model Is T Cell Mediated and Inhibited by a Combination of Cyclosporine and Rapamycin

Abstract: We have analyzed the mechanism of human endothelial injury in a human peripheral blood lymphocytesevere combined immunodeficient (huPBL-SCID) mouse/human skin graft model of allograft injury and examined the effect of immunosuppressive drugs on this process. In this model , split-thickness human skin containing the superficial dermal microvessels was grafted onto immunodeficient C.B-17 SCID or SCID/beige mice and allowed to heal. Human peripheral blood mononuclear cells (PBMCs) allogeneic to the skin , when su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…In parallel with growth inhibition, Cyclosporin A reduces the production of pro-inflammatory effector molecules by keratinocytes (Iversen et al, 1996;Kaplan et al, 1995;Won et al, 1994). Fibroblasts, endothelial cells, and antigen-presenting cells may also be important targets of Cyclosporin A in psoriasis (Fukuoka et al, 1998;Murray et al, 1998;Wong et al, 1993). Effects on any of these populations could contribute to the antiproliferative and anti-inflammatory effects of Cyclosporin A.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with growth inhibition, Cyclosporin A reduces the production of pro-inflammatory effector molecules by keratinocytes (Iversen et al, 1996;Kaplan et al, 1995;Won et al, 1994). Fibroblasts, endothelial cells, and antigen-presenting cells may also be important targets of Cyclosporin A in psoriasis (Fukuoka et al, 1998;Murray et al, 1998;Wong et al, 1993). Effects on any of these populations could contribute to the antiproliferative and anti-inflammatory effects of Cyclosporin A.…”
Section: Discussionmentioning
confidence: 99%
“…To further establish whether IL-11 could increase survivin protein in vivo, we used a human skin xenograft model developed in severe combined immunodeficient (SCID)/beige mice (Murray et al, 1998). Immunostaining of human skin grafts with survivin Ab demonstrated that intradermal injection of IL-11 into human skin grafts increased survivin protein expression in these grafts (Fig.…”
Section: Il-11 Up-regulates Survivin Mrna and Protein In Vivomentioning
confidence: 99%
“…Human skin was transplanted to SCID/beige mice as previously described under a protocol approved by Yale Animal Care and Use Committee (Murray et al, 1998). In brief, superficial portions of the skin were harvested in 0.5-mmthick sheets using a Goulian dermatome knife, gauge size, 0.016 (Weck, Research Triangle Park, North Carolina), and cut into approximately 1 cm 2 pieces, which were kept in RPMI 1640 (Life Technologies) at 4°C until transplantation (not longer than 6 hours).…”
Section: Skin Graftingmentioning
confidence: 99%
“…In an effort to improve human cell engraftment and function in immunodeficient mice, Pober and colleagues initiated a series of studies using CB17-scid mice co-expressing the beige (Lyst bg ) mutation (SCID/beige). [59][60][61] The beige mutation disrupts a gene required for lysosomal trafficiking and results in impaired NK cell function. 62,63 The use of SCID/beige mice allowed engraftment of human PBMC without depletion of NK cells, but still required the injection of high numbers of cells (1310 8 -3310 8 cells).…”
Section: Human Skin Allograftsmentioning
confidence: 99%
“…64 Injection of human PBMC or T-cell lines into SCID/beige mice bearing human skin allografts produced allograft injury that was characterized by vascular damage, and this injury was mediated by human CD4 and CD8 T cells. [59][60][61] The SCID/beige model has since proven useful in characterizing allograft injury mediated by human T cells. Inhibition of human T-cell function by treatment of skin allograft bearing SCID/ beige mice with a combination of cyclosporine and rapamycin significantly reduced the level of human cell infiltrate and microvascular damage.…”
Section: Human Skin Allograftsmentioning
confidence: 99%